Global burden of polycystic ovary syndrome among women of childbearing age, 1990–2021: a systematic analysis using the global burden of disease study 2021 - Yaping Meng; Ting Zhao; Rui Zhang; Xiaoyan Zhu; Chao Ma; Qin Shi (Frontiers in Public Health)
BackgroundThe escalating global incidence of polycystic ovary syndrome (PCOS) necessitates a thorough examination of its epidemiological trends and sociodemographic correlations. Our study bridges this gap by analyzing the global impact of PCOS among women of childbearing age (WCBA) from 1990 to 2021, aiming to inform strategies for enhanced prevention and management.MethodsWe extracted data from the Global Burden of Disease Study 2021 (GBD 2021), focusing on the burden of PCOS among women aged 15–49 years. We assessed incidence, prevalence, and disability-adjusted life years (DALYs) trends using the estimated annual percentage change (EAPC) and explored the link between PCOS burden and sociodemographic index (SDI).ResultsIn 2021, the prevalence cases of PCOS worldwide were 65.77 million, the incidence cases were 1,175.07 thousand, and the DALYs cases were 576.05 thousand. Compared with 1990, the percentage changes were 89, 49, and 87%, respectively. The EAPCs indicated upward trends in prevalence and DALYs rates, with a less pronounced increase in incidence rates. The middle SDI region had the highest PCOS case numbers, and the 45–49 age group in this region experienced the most significant burden increase. A strong positive correlation existed between PCOS prevalent rates and SDI (r = 0.582, p < 0.001).ConclusionThe global burden of PCOS among WCBA has significantly increased over the past three decades, particularly in the 45–49 age group in middle SDI regions. The correlation between PCOS prevalent rates and SDI highlights the role of socio-economic factors in PCOS epidemiology. Tailored prevention and management strategies are crucial for reducing the global burden of PCOS and improving female health outcomes.